2013
DOI: 10.7314/apjcp.2013.14.5.2967
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal Ewing Sarcomas in Late Adolescence and Adults: A Study of 37 Patients

Abstract: Background: Extraskeletal Ewing sarcoma (EES)/primitive neuroectodermal tumours (PNET) are rare soft tissue sarcomas. Prognostic factors and optimal therapy are still unconfirmed. Materials and Methods: We performed a retrospective analysis on patients to explore the clinic characteristics and prognostic factors of this rare disease. A total of 37 patients older than 15 years referred to our institute from Jan., 2002 to Jan., 2012 were reviewed. The characteristics, treatment and outcome were collected and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
(69 reference statements)
1
18
1
Order By: Relevance
“…A significant number of patients in our study (8/23, 35%) also had metastatic disease at presentation, similar to the study by Tao et al 18 of 37 patients who found metastases at presentation in 43% patients, indicating the necessity for complete staging at the time of initial diagnosis. The most common site of metastases in our study was the lung (27%), which is in agreement with the existing literature.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…A significant number of patients in our study (8/23, 35%) also had metastatic disease at presentation, similar to the study by Tao et al 18 of 37 patients who found metastases at presentation in 43% patients, indicating the necessity for complete staging at the time of initial diagnosis. The most common site of metastases in our study was the lung (27%), which is in agreement with the existing literature.…”
Section: Discussionsupporting
confidence: 78%
“…3 The 5-year survival in the study by El Weshi et al 3 was 46% with 35 deaths out of 57 patients. The 3-year survival in the study by Tao et al 18 was 43%. Of the 23 patients under follow-up in our study, 9 (39%) were deceased at the time of the last follow-up at a median interval of 10 months (range, 6-20 months).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The patients had obviously better disease even those had been received only surgical resection. Extraskeletal Ewing's sarcoma considers as a poor prognostic factor (Tural et al, 2012;Somarouthu et al, 2014), however the outcome of the patients in our study that mainly were skeletal was worse than that Tao HT et al (2013) reported in extraskeletal Ewing's sarcoma in China. In this study median event free survival and overall survival for entire group were 15.8 months and 30.2 months respectively.…”
Section: Discussioncontrasting
confidence: 49%